International investment income: Patterns, drivers, and heterogeneous sensitivities - Giovanni Donato; Cédric Tille (Graduate Institute of International and Development Studies, 2024)
Financial globalization has led to a large increase in international asset holdings. While the rise of associated dividend and interest flows has until now been muted by the decreasing trend in interest rates, this pattern could change, leading to a larger role of investment income flows in the balance of payments. We use a broad sample of countries to document the heterogeneous evolution of the various components of investment income flows, with a rising role of FDI and equity income, especially in advanced economies. We then assess the impact of various variables on yields with a panel analysis. Various drivers have highly heterogeneous effects across investment categories and country groups, often impacting the yields on both assets and liabilities. This translates into substantial heterogeneity in the response of countries' income balance, due to different compositions of asset and liabilities. This heterogeneity is amplified if we consider country-specific estimates in complement to the panel ones. Focusing on the impact of changes in interest rates, we find that higher rates only had a limited impact in the 2013 taper tantrum, investment income balances are likely to benefit from higher US rates in the current phase of higher rates, with offsetting effects of higher domestic rates.
Keywords: F32; F36; F40; 330; Financial integration; primary investment income flows; interest rates; exchange rates